STRENGTHENING ADOLESCENT IDENTITY AWARENESS AND SELF-POTENTIAL RECOGNITION THROUGH GROUP COUNSELING - Nur Hermatasiyah; Putri Nurina (CV. TOTUS TUUS, 2026)
Adolescents are vulnerable to identity confusion and low self-confidence when social pressure and repeated comparison with peers obscure their understanding of personal strengths. This study examined the implementation of group counseling to strengthen identity awareness and self-potential recognition among junior high school students. The study used Guidance and Counseling Action Research with a qualitative descriptive approach. Three Grade VIII students were selected from the personal-domain results of the General Problem Checklist (AUM Umum). Data were collected through participatory observation, brief interviews, documentation, self-assessment, and group reflection. The intervention comprised four counseling sessions addressing self-introduction, exploration of strengths, reflection on social comparison, and formulation of personal development commitments. The findings indicated observable improvement in students’ willingness to describe themselves, identify nonacademic as well as academic strengths, express feelings, accept limitations, and establish realistic development goals. Group interaction provided corrective feedback and emotional support that reduced deficit-focused self-evaluation and encouraged more balanced self-perceptions. Within the limits of a small action-research group, the study indicates that structured group counseling can support healthier identity construction and more purposeful recognition of adolescent potential.